Extended MASTAR modeling of DIBL in UTB and UTBB SOI MOSFETs - Mohd Khairuddin, Md Arshad, Dr.; Raskin, Jean-Pierre, Prof.; Kilchytska, Valeriya, Dr.; Andrieu, François, Dr.; Scheiblin, Pascal; Faynot, O.; Flandre, Denis, Prof. (Institute of Electrical and Electronics Engineers (IEEE), 2013)
Link to publisher's homepage at http://ieeexplore.ieee.org/